2009
DOI: 10.1021/cm9000569
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Photoelectron Spectroscopy and in Situ X-ray Absorption Spectroscopy Studies on Reversible Insertion/Desertion of Dicyanamide Anions into/from Manganese Oxide in Ionic Liquid

Abstract: Pseudocapacitive characteristics of manganese (Mn) oxide were recognized in aprotic ionic liquid (IL), namely, butylmethylpyrrolidinium−dicyanamide (BMP−DCA), within a potential window of 3 V. The electrochemical energy storage mechanism was examined using X-ray photoelectron spectroscopy and in situ X-ray absorption spectroscopy. It was confirmed that the DCA− anions, instead of the bigger BMP+ cations, were the working species that compensate the Mn valent state variation upon charging and discharging in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(56 citation statements)
references
References 65 publications
(86 reference statements)
1
52
2
Order By: Relevance
“…This behavior suggests that faradic phenomena occur during the charge-storage mechanism. The presence of redox waves during the charge/discharge process was already reported for several MnO 2 -based electrodes (Hu & Tsou, 2002;Brousse et al, 2006;Ghodbane & Favier 2009;Chang et al, 2009;Lee et al, 2010). The electrochemical experiments in their work demonstrate that the crystallographic form of MnO 2 influences the electrochemical performance, and the small tunnel of -MnO 2 was not suitable to store cations, while the large tunnel size of -MnO 2 favors the storage of cations Cheng et al, 2010).…”
Section: +-2mentioning
confidence: 68%
See 1 more Smart Citation
“…This behavior suggests that faradic phenomena occur during the charge-storage mechanism. The presence of redox waves during the charge/discharge process was already reported for several MnO 2 -based electrodes (Hu & Tsou, 2002;Brousse et al, 2006;Ghodbane & Favier 2009;Chang et al, 2009;Lee et al, 2010). The electrochemical experiments in their work demonstrate that the crystallographic form of MnO 2 influences the electrochemical performance, and the small tunnel of -MnO 2 was not suitable to store cations, while the large tunnel size of -MnO 2 favors the storage of cations Cheng et al, 2010).…”
Section: +-2mentioning
confidence: 68%
“…In addition, the presence of other metal cations in the tunnel in advance hinders the diffusion and storage of the electrolyte cations leading to a decrease in capacitance. More recently, further research on the tunnel storage of MnO 2 even revealed that the aprotic ionic liquids anions with the far bigger diameters than that of alkaline metal ion, could also be stored in the tunnels of MnO 2 (Xu et al 2010 ;Chang et al, 2009;Lee et al, 2010). More recently, a multivalent cation storage mechanism was proposed by Xu et al, they think not only univalent alkaline metal cations could store in the tunnels of MnO 2 , bivalent alkaline-earth metal cations also are present in it .…”
Section: +-2mentioning
confidence: 99%
“…And their cycle-ability was not enough to actual application. Aprotic ILs were tried as electrolyte for pseudoelectrode in some cases [66]. The pseudomaterial was manganese dioxide (MnO 2 ), and the IL was …”
Section: Other Approaches Of Ionic Liquid As Liquid Electrolytementioning
confidence: 99%
“…And the electroreflectance spectroscopies [47] have provided information about the orientation of molecules in adsorbed overlayers. X-ray absorption spectroscopies [48,49] were employed to determine the coordination numbers of adsorbed species and the substrate-adsorbate and adsorbate-adsorbate bond lengths. Ab initio-based computations on the property of electrode materials and continuum modeling have been incorporated to provide theoretical insights and predictions [50,51].…”
Section: Techniques For Studying Interfacial Properties In Ilsmentioning
confidence: 99%